The meeting – seeing and being affected by the patient: A reason for ethical competence among health personnel - Bjerga, Grethe Heidi; Kaldestad, Kari; Rossavik, Bente; Jensen, Anne Ree; Koskinen, Camilla Ann-Louise (Nordisk Tidsskrift for Helseforskning, 2023)
The purpose of this caring science study is to deepen the understanding of health personnel’s experiences of challenges and the fundamental basis for maintaining ethical competence in clinical practice. The study has a qualitative design. The methodology is hermeneutic application research. Twelve participants from several professions were divided into two groups for dialogue and reflection about ethical competence. Systematic text condensation was used as an analysis method. The analysis resulted in four themes, ethics are challenged in complex clinical situations, to create space for reflection, to see the human being, and to be touched by the patient. The results confirm that the encounter between health personnel and the patient is significant and that the encounter itself is immanent ethics. Health personnel work with a tension between a system characterized by busyness and chores and seeing the patient as a human being and being overwhelmed by his or her suffering. In this field of tension, health personnel can be in the movement of becoming and reflecting on what promotes and maintains ethical competence.
Keywords: Ethical competences; hermeneutic application research; Health professionals; Systematic text condensation